A bench evaluation of fraction of oxygen in air delivery and tidal volume accuracy in home care ventilators available for hospital use - Baboi, Loredana; Subtil, Fabien; Guérin, Claude (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Background: Turbine-powered ventilators are not only designed for long-term ventilation at home but also for hospital use. It is important to verify their capabilities in delivering fraction of oxygen in air (FIO2) and tidal volume (VT). Methods: We assessed the FIO2 accuracy and the VT delivery in four home care ventilators (HCV) on the bench. The four HCV were Astral 150, Elisée 150, Monnal T50 and Trilogy 200 HCV, which were connected to a lung model (ASL 5000). For assessing FIO2 accuracy, lung model was set to mimic an obstructive lung and HCV were set in volume controlled mode (VC). They supplied with air, 3 or 15 L/min oxygen and FIO2 was measured by using a ventilator tester (Citrex H4TM). For the VT accuracy, the lung model was set in a way to mimic three adult configurations (normal, obstructive, or restrictive respiratory disorder) and one pediatric configuration. Each HCV was set in VC. Two VT (300 and 500 mL) in adult lung configuration and one 50 mL VT in pediatric lung configuration, at two positive end expiratory pressures 5 and 10 cmH2O, were tested. VT accuracy was measured as volume error (the relative difference between set and measured VT). Statistical analysis was performed by suing one-factor ANOVA with a Bonferroni correction for multiple tests. Results: For Astral 150, Elisée 150, Monnal T50 and Trilogy 200, FIO2 averaged 99.2%, 93.7%, 86.3%, and 62.1%, respectively, at 15 L/min oxygen supplementation rate (P